2020
DOI: 10.1155/2020/3431828
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-34a and Bone Mineral Density of Brazilian Very-Old Adults

Abstract: The human aging is marked by several body changes, including in bone mineral density (BMD). Research shows that microRNAs are important modulators of bone metabolism. The present research aims to analyze the whole blood concentration of 10 selected microRNAs (miRs) and their association with absolute and relative scores of BMD in specific osseous site of Brazilian very-old adults. Forty noninstitutionalized and apparently healthy, very old (≥80 years) outpatients were eligible for research. Anthropometry, bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…None of the studies on sarcopenia defined the study design. Most of the studies (68%) were conducted in China, but participant ethnicity is stated in very few studies (25%) [ 29 , 30 , 35 , 42 , 43 , 52 , 53 , 54 , 55 , 57 , 60 , 65 , 81 , 82 ], thus limiting the generalizability of findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…None of the studies on sarcopenia defined the study design. Most of the studies (68%) were conducted in China, but participant ethnicity is stated in very few studies (25%) [ 29 , 30 , 35 , 42 , 43 , 52 , 53 , 54 , 55 , 57 , 60 , 65 , 81 , 82 ], thus limiting the generalizability of findings.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (17%) recruited younger participants in healthy control groups [ 38 , 41 , 42 , 44 , 47 , 59 , 60 , 71 , 78 ] and did not match for age, causing potential selection bias. Almost all the studies considered female osteoporotic and sarcopenic patients (76%), but 14/59 studies also included male patients [ 34 , 38 , 50 , 52 , 53 , 58 , 59 , 60 , 61 , 62 , 66 , 73 , 77 , 82 , 83 ]. Twelve studies on osteoporosis and two on sarcopenia did not state sex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 47 ) Several studies have found miR‐34a to increase with age in EVs secreted by BMSCs, ( 48 , 49 ) and miR‐34a suppresses osteoblast differentiation as well as bone formation by differentiated osteoblasts. ( 50 , 51 ) Total circulating levels of miR‐34a (not solely EV‐derived miR‐34a) are inversely correlated with bone mineral density in older adults, ( 52 ) and circulating miR‐34a is increased with ovariectomy and positively correlated with bone loss in rodents. ( 53 ) Furthermore, EVs from aged bone matrix transfer microRNAs such as miR‐483‐5p and miR‐2861, which stimulate vascular calcification and bone marrow adipogenesis.…”
Section: Introductionmentioning
confidence: 99%